Impact of Climate Change and Aquatic Salinization on Mangrove Species and Poor Communities in the Bangladesh Sundarbans - Dasgupta, Susmita; Sobhan, Istiak; Wheeler, David (World Bank, Washington, DC, 2016)
This paper investigates possible impacts of climate change on the poor communities of the Bangladesh Sundarbans via changes in aquatic salinity and mangrove species. The implications for poor communities are assessed by computing changes in high-value mangrove species for the five sub-districts in the Sundarbans. The results of the impact analysis indicate highly varied patterns of gain and loss across the five sub-districts. Overall, however, the results indicate that salinity-induced mangrove migration will have a strongly regressive impact on the value of timber stocks because of the loss of the highest value timber of Heretiera fomes. In addition, augmented potential for honey production is likely to increase conflicts between humans and wildlife in the region.